Public Sector Financial Performance in Indonesia: Concepts and Regulations - Tumangkeng, Steeva Y. L.; Anderson G. Kumenaung; Debby Ch. Rotinsulu; Joy E. Tulung; Ita P. F. Rorong (Open Access Indonesia Journal of Social Sciences, 2022)
Improving the public sector's financial performance is crucial to encouraging rapid economic growth throughout Indonesia. This paper aims to understand the essentials of the concepts and regulations of the public sector financial performance management in Indonesia. This study examines the performance of public sector organizations in Indonesia, especially looking at the definitions and regulations that form the basis of implementing this performance. The identification of the performance of the public sector in this paper seeks to see the basic concepts that serve as guidelines and the laws and regulations that form the background of the achievements of public organizations in Indonesia. In conclusion, it is revealed that the financial performance of the public sector in Indonesia refers to the applicable laws and regulations starting from the fundamental law, namely the 1945 Constitution, especially Article 23C, followed by several laws, government regulations, presidential regulations, and ministerial finance regulations. The measurement of public sector financial performance is regulated and determined by the Ministry of Finance through budget implementation performance indicators, which are seen from four aspects and twelve main indicators.